Peut-on parler d’une culture professionnelle des éducateurs ? - Michel Chauvière (Sociétés et Jeunesses en Difficulté)
The author first aims at specifying and problematising the notion of professional culture in éducateurs (french social workers specialised in youth work and/or care work) and uses for that purpose an open definition of culture, dynamised by the notion of « social world ». Two dialectically involved aspects of culture are then approached : on one side, what gathers, what is shared, and also what is used to protect the ingroup of professionals from the outgroup ; on the other side, the questions asked from outside that challenge professionals, blur the shared categories, split and divide inside. Data are drawn either from the author’s observations or from different studies already published, as well as from his long time companionship whith the éducateurs in the context of juvenile justice or social work.